Measuring social phobia symptoms in a community sample of adolescents: An examination of the psychometric properties of the SPAI-23 - Apostolakis, Markos; Theodorou, Marios; Neophytou, Klavdia; Panayiotou, Georgia (Frontiers in Psychology, 2022)
A number of studies to date examine dimensions of social phobia and anxiety in adolescents. A variety of tools has been developed, along with their abbreviated versions, that are used to assess Social Anxiety (SA) but little research has been devoted to the types of fears they each assess. Due to differences in the content of the multitude of instruments, different aspects of SA are addressed and this leads to confusion when the relationship between SA and other constructs is being investigated. The aim of the present study was to examine the psychometric properties of the abbreviated Social Phobia and Anxiety Inventory SPAI-23 in Greek-Cypriot community adolescents and describe dimensions of social fears at that age. Seven hundred twenty-one adolescent students from Cyprus, (Mean Age: 15.5, Range: 13–19, SD: 1.12, 64% female) participated in the study. Participants completed, among others, an abbreviated version of the Social Phobia and Anxiety Inventory (SPAI-23). Exploratory Factor Analysis on the SPAI-23 revealed a quite similar structure to the original questionnaire (SPAI). Three Social Phobia factors, describing distinct socially fearful situations, were identified (Performance, Interaction, and Presence in a social context) and one Agoraphobia factor after the evaluation of alternative solutions. Findings were verified by means of Confirmatory Factor Analysis, testing alternative models. Overall, findings were in line with recent evidence on youth samples, and contribute to significant insights towards more sophisticated and personalized assessments.